Philosophy of Fatwa Muhammadiyah and Nahdatul Ulama Against Changes in Worship Activities Due to Covid 19 - Syafaruddin, Syafaruddin; Nasution, Hasan Bakti; Tanjung, Dhiauddin (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2023)
This study aimed at discussing the philosophical basis of the fatwa of Muhammadiyah and Nahdatul Ulama at Labuhanbatu Regency regarding changes in worship activities due to Covid 19. This study was descriptive field research. Data collection techniques used are interviews and documentation. The analysis technique used is Miles and Huberman. The findings of this study were the philosophy of the Muhammadiyah fatwa regarding changes in worship activities due to covid 19 based on the hifdzu al-nafs wa al-dîn command. The obligation to look after oneself and is inseparable. Meanwhile, the philosophy of Nahdatul Ulama's fatwa was based on the maqâshid al-syarî`ah principle, namely jalbu al-mashâlih wa dar’u al-mafâsid. Nahdatul Ulama, the largest Islamic organization, comprehends that worship should not neglect the soul's safety. The basis of this philosophy can be observed from the concept of the `indal khauf prayer. Prayer is an obligatory worship, but in conditions where the safety of the soul is threatened, the practice of praying can adjust to the conditions; even if this dharurat condition is drastic, the scholars allow fî ayyi amkân prayer practice. Penelitian ini membahas landasan filosofi fatwa Muhammadiyah dan Nahdatul Ulama Kabupaten Labuhanbatu terhadap perubahan aktivitas ibadah akibat covid 19. Studi ini adallah penelitian lapangan yang berifat deskriptif. Teknik pengumpulan data yang digunakan adalah wawancara dan dokumentasi. Teknik analisa yang digunakan adalah Miles dan Huberman. Temuan penelitian ini adalah filosofi fatwa Muhammadiyah terhadap perubahan aktivitas ibadah akibat covid 19 didasarkan pada perintah hifdzu al-nafs wa al-dîn. Kewajiban menjaga diri dan agama saling bersinergi tidak bisa dipisah-pisahkan antara satu dengan lainnya. Sedangkan filosofi fatwa Nahdatul Ulama didasari oleh prinsip maqâshid al-syarî`ah yakni jalbu al-mashâlih wa dar’u al-mafâsid. Nahdatul Ulama sebagai organisasi Islam terbesar sangat paham sekali bahwa ibadah tidak boleh mengesampingakan keselamatan jiwa. Dasar filosofi ini terlihat pada konsep salat `indal khauf. Ibadah shalat merupakan ibadah yang sangat wajib dan harus dilaksanakan, namun dalam kondisi keselamatan jiwa terancam maka praktek ibadah shalat ini bisa menyesuaikan kondisi, bahkan jika kondisi darurat ini sudah sangat parah maka para ulama membolehkan shalat fî ayyi amkân.